Effect of Heat-Treating on Microstructure and High Cycle Bending Fatigue Behavior of AZ91 and AZE911 Magnesium Alloys - Ahmad Yousefi Parchin Oliya; Mohammad Azadi; Mohammad Sadegh Aghareb Parast; Mehdi Mokhtarishirazabad (Advances in Materials Science and Engineering)
This article investigates the influences of heat-treating on the microstructures and the high cycle fatigue (HCF) properties of AZ91 and AZE911 (AZ91 + 1%RE) magnesium alloys. For such an objective, AZ91 and AZE911 alloys were used after solution treatment at 415°C for 5 hours aged at 215°C for 3 hours and at 215°C for 5 hours, respectively. To investigate the HCF behavior, a rotational bending fatigue test was performed with stress ratio (R) −1 and frequency of 100 Hz at room temperature. Optical microscopy (OM) study demonstrates that heat treatment leads to a reduction in grain size and transformation of continuous and discontinuous precipitations into needle-shaped precipitations, which are located on the grains of the alpha phase. Scanning electron microscopy (SEM) showed both marks of quasicleavage and cleavage on the fracture surface of specimens. These planes indicated the brittle behavior of the fracture. Moreover, in heat-treated specimens, the size of cleavage patterns was smaller, and microcracks were shorter. These behaviors affected the strength of the material and the fatigue lifetime. The results of mechanical tests show a negligible influence of heat-treating on the HCF behaviors of AZ91-T6 and AZE911-T6 alloys. Stress-lifetime curves (S-N) show an increase in fatigue strength in 3.8 × 105 fatigue cycles, from 95 MPa to 125 MPa for the AZ91-T6 alloy and from 125 MPa to 155 MPa for the AZE911-T6 alloy, after heat treatment.